Paradigmi dello Sviluppo e Approccio Relativista - Bassi, Marco (Antropologia Pubblica, 2018)
In this article the author builds on the notion of “paradigm of development” to provide analytic instruments for the institutional analysis of international development. He identifies the following four main paradigms, each rooted in different disciplines and ethical foundations:1) economic growth; 2) social equity; 3) environmental sustainability; 4) beneficiaries’ active role. Each paradigm implies different and measurable objectives, to be achieved by specific methodological approaches. The various paradigms give different consideration to relevance of specific articulations of culture, formal or informal norms and local conditions. It is accordingly possible to classify them based on their relativist attitude. The economic growth paradigm assumes generalized positive gain for the public. The beneficiaries of development are not really defined: they are an imagined community that cannot take any direct role in the design and implementation of programmes and project. As such, this paradigm stands in opposition to the highly relativist fourth paradigm that instead requires specific communities to take an active decisional role on the development process. Equally diverging along the relativist gradient are the priorities defined by different sets of human rights, that on the whole provide the internationally agreed ethical dimension of international development. The transversal responsibilities for the application and promotion of the internationally agreed human rights have over the last two decades facilitated a process of hybridization of the development paradigms. Hybridization and inhomogeneity thus pervade the organizational culture of each international organisation, opening up space for both manipulations and negotiations.